2010
DOI: 10.1093/deafed/enq012
|View full text |Cite
|
Sign up to set email alerts
|

Deaf Adults' Reasons for Genetic Testing Depend on Cultural Affiliation: Results From a Prospective, Longitudinal Genetic Counseling and Testing Study

Abstract: This article examines the relationship between cultural affiliation and deaf adults' motivations for genetic testing for deafness in the first prospective, longitudinal study to examine the impact of genetic counseling and genetic testing on deaf adults and the deaf community. Participants (n = 256), classified as affiliating with hearing, Deaf, or both communities, rated interest in testing for 21 reasons covering 5 life domains. Findings suggest strong interest in testing to learn why they are deaf, but litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Genetic testing would be welcomed even by communities in which genetic counseling and testing are not usually applied, if it is offered in accordance with their cultural norms and beliefs. Therefore, while Middleton et al [12] identified predominantly negative attitudes toward genetic research and genetic testing for deafness, more current research demonstrates a growing interest in the deaf community in pursuing genetic testing [13,14,22]. The reasons for pursuing genetic testing vary, as described in these studies, but a strong motivation is to learn why they are deaf.…”
Section: Discussionmentioning
confidence: 93%
“…Genetic testing would be welcomed even by communities in which genetic counseling and testing are not usually applied, if it is offered in accordance with their cultural norms and beliefs. Therefore, while Middleton et al [12] identified predominantly negative attitudes toward genetic research and genetic testing for deafness, more current research demonstrates a growing interest in the deaf community in pursuing genetic testing [13,14,22]. The reasons for pursuing genetic testing vary, as described in these studies, but a strong motivation is to learn why they are deaf.…”
Section: Discussionmentioning
confidence: 93%
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…Exploratory and pilot studies have identified interest in furthering research as among the primary reasons given for testing for genetic causes of sudden cardiac death, smoking susceptibility, deafness, and a variety of cancers [28][29][30][31][32]. For quantitative studies involving genetic tests for conditions including BRCA, Alzheimer's, and Pancreatitis, testing intention has previously been associated with wanting to help advance research [33][34][35][36][37].…”
Section: Doi: 107243/2054-992x-4-4mentioning
confidence: 99%